Familial gastrointestinal stromal tumors, lentigines, and café‐au‐lait macules associated with germline c‐kit mutation treated with imatinib. (February 2017) - Gupta, Divya; Chandrashekar, Laxmisha; Larizza, Lidia; Colombo, Elisa A.; Fontana, Laura; Gervasini, Cristina; Thappa, Devinder M.; Rajappa, Medha; Rajendiran, Kalai Selvi; Sreenath, Gubbi Shamanna; Kate, Vikram
Abstract: Background: Familial lentiginosis syndromes are characterized by a wide array of manifestations resulting from activation of molecular pathways which control growth, proliferation, and differentiation of a broad range of tissues. Familial gastrointestinal stromal tumors (GISTs) are often accompanied by additional features like hyperpigmentation, mastocytosis, and dysphagia. They have been described with mutations in c‐kit (most commonly), platelet‐derived growth factor receptor A, neurofibromatosis‐1, and succinate dehydrogenase genes. Materials and Methods: We report on molecular characterization and tumor histopathology of two siblings in whom lentigines and café‐au‐lait macules were present along with multifocal GIST. Immuhistochemical analysis of CD34 and CD117 was performed on GIST biopsy samples from both siblings, while c‐kit mutational analysis was done by PCR and direct sequencing on DNA from peripheral blood leukocytes of all family members and from paraffin‐embedded gastric biopsy specimens of affected siblings. Results: Histopathology revealed positive expression of CD117 and CD34. Mutational analysis showed the germline c.1676T>C mutation in c‐kit exon 11, (p.(Val559Ala)), in the peripheral blood of both siblings and a second exon 11 mutation, c.1669T>A (p.(Trp557Arg)) in the tumor biopsy of one of them. Initiation of imatinib treatment resulted in striking resolution of their hyperpigmentation and a stable gastrointestinal disease in one of them. Conclusions: A c‐kit mutational test in familial GISTs is indicated before initiation of imatinib therapy, as it can help predict tumor response to treatment.